2012
DOI: 10.1016/j.nut.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glutathione of HIV+ patients responded positively and differently to dietary supplementation with cysteine or glutamine

Abstract: An increase in GSH may be attained by NAC or Gln supplementation, with NAC acting by increasing cysteine levels and Gln likely acting by replenishing the glycine pool (trial registered at http://www.clinicaltrials.gov, identifier NCT00910442).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 28 publications
1
61
1
3
Order By: Relevance
“…Nine of the 16 studies selected were excluded from outcome 2 because of the absence of an HIV-infected non-ART group [29,[30][31][32][33][36][37][38][39] (Figure 1). Table 2 describes the characteristics of the 7 studies included in outcome 2.…”
Section: Outcomementioning
confidence: 99%
See 3 more Smart Citations
“…Nine of the 16 studies selected were excluded from outcome 2 because of the absence of an HIV-infected non-ART group [29,[30][31][32][33][36][37][38][39] (Figure 1). Table 2 describes the characteristics of the 7 studies included in outcome 2.…”
Section: Outcomementioning
confidence: 99%
“…Nine of the 12 studies reported that the mean Hcy concentration was greater in HIV-infected individuals compared to controls. Only five [33,34,36,38,39] and four [33,36,38,39] of the included studies described quantitative folate and vitamin B12 data, respectively (Table 1). A meta-analysis performed on outcome 1 indicated that the plasma Hcy levels in HIV-infected patients were 2.05 µmol/L higher than the plasma Hcy levels in uninfected controls (95%CI: 0.13-4.01, P < 0.01; [30] Norway 15/21 CS 9.2 ± 7.3 9.0 ± 5.0 ---Naisbitt et al [31] England 33/33 CS 11.9 ± 4.7 14.5 ± 5.6 ---Bernasconi et al [32] Swaziland 80/73 COS 7.6 ± 3.6 8.…”
Section: Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…The presence of HAART showed some benefi cial effects on β-carotene plasma levels but not on the other antioxidant markers [ 2 ]. Among those were glutathione (GSH) and its precursors [ 3 ]. GSH ( L -y-glutamyl-L -cysteinyl-glycine) is the major intracellular hydro-soluble antioxidant agent representing important functions in biochemical processes and cell control, specially the antioxidant and immune defenses [ 4 ].…”
Section: The Role Of Gsh On Antioxidant Actionsmentioning
confidence: 99%